El "De utilitate credendi" y la teoría dialógica de san Agustín - Pascual LC, Fernando (Alpha Omega, 2011)
This article analyses St. Agustine’s "De utilitate credendi". It considers ideas and affirmations that are important aspects of the bishop of Hippo’s dialogic theory. After reflecting on the different contributions of the present text, we can see the importance of faith and authority on the path which leads human beings to the true religion, where it’s possible to encounter God and reach happiness, for which the human heart yearns.